Development of a Circular Supply Chain Model in the Retail Industry to Minimize Waste and Maximize Resource Recovery - Hedi Pandowo (PT. ELSHAD TECHNOLOGY INDONESIA, 2026)
The Indonesian retail industry generates approximately 69.9 million tons of waste per year with a recycling rate of merely 6.5–10%, exposing deep inefficiencies in the prevailing linear